The Effect of Prenatal Yoga on the Length of the First Stage of the Active Phase in Primigravida Mothers at Ria Trisnawati's Independent Practice in Palembang - Franciska, Yunetra; Yuka, Aprillia Ayu Shinta; Yanuar, Nada Romadona (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Pregnancy and childbirth are periods where a woman has a golden opportunity to feel and realize the tremendous power within herself. In the birth process, you have to go through all the stages, a long 1st Stage can harm the fetus and the mother. The thinning and opening of the cervix is ​​a sign of the start of the labor process. It is estimated that primigravid women will experience cervical dilation of at least 1 cm/hour. In Primigravida mothers, the average length of labor during the active phase is 5.8 hours or 348 minutes for the Active phase. Currently, there are many ways to speed up, ease and make the labor process more comfortable during labor, namely hypnobirthing, pelvic rocking, aroma therapy, warm water compresses and yoga. Prenatal yoga is a combination of physical poses (called asanas), breathing techniques (called pranayama), meditation, and relaxation to strengthen mentally and physically in facing the birth process. If the pain in a mother who is about to give birth can be eliminated by carrying out a relaxation process, it will facilitate labor that is triggered by stress, so that the labor process can be carried out naturally, without ending in labor. This study aims to determine the effect of prenatal yoga on the length of the first stage of the active phase in primigravida mothers at the Independent Practice of Midwife Ria Trisnawati Palembang. Sampling was taken using the Purposive Sampling technique. The results of the study showed that prenatal yoga had an effect on the length of the first active phase of primigravida mothers in the independent practice of midwife Ria Tisnawati Palembang with a p value of 0.006 (p < α 0.005) and an OR of 10.0000